Gene Expression and Cell Cycle Arrest Mediated by Transcription Factor DMP1 Is Antagonized by D-Type Cyclins through a Cyclin-Dependent-Kinase-Independent Mechanism - Inoue, Kazushi (American Society for Microbiology, 1998)
A novel 761-amino-acid transcription factor, DMP1, contains a central DNA binding domain that includes three imperfect myb repeats flanked by acidic transactivating domains at the amino and carboxyl termini. D-type cyclins associate with a region of the DMP1 DNA binding domain immediately adjacent to the myb repeats to form heteromeric complexes which detectably interact neither with cyclin-dependent kinase 4 (CDK4) nor with DNA. The segment of D-type cyclins required for its interaction with DMP1 falls outside the “cyclin box,” which contains the residues predicted to contact CDK4. Hence, D-type cyclin point mutants that do not interact with CDK4 can still bind to DMP1. Enforced coexpression of either of three D-type cyclins (D1, D2, or D3) with DMP1 in mammalian cells canceled its ability to activate gene expression. This property was not shared by cyclins A, B, C, or H; did not depend upon CDK4 or CDK2 coexpression; was not subverted by a mutation in cyclin D1 that prevents its interaction with CDK4; and was unaffected by inhibitors of CDK4 catalytic activity. Introduction of DMP1 into mouse NIH 3T3 fibroblasts inhibited entry into S phase. Cell cycle arrest depended upon the ability of DMP1 to bind to DNA and to transactivate gene expression and was specifically antagonized by coexpression of D-type cyclins, including a D1 point mutant that does not bind to CDK4. Taken together, these findings suggest that DMP1 induces genes that inhibit S phase entry and that D-type cyclins can override DMP1-mediated growth arrest in a CDK-independent manner.